Complicated Postoperative Flat Back Deformity Correction With the Aid of Virtual and 3D Printed Anatomical Models: Case Report - Fayad, Jennifer; Turbucz, Mate; Hajnal, Benjamin; Bereczki, Ferenc; Bartos, Marton; Bank, Andras; Lazary, Aron; Eltes, Peter Endre (Frontiers in Surgery, 2021)
Introduction: The number of patients with iatrogenic spinal deformities is increasing due to the increase in instrumented spinal surgeries globally. Correcting a deformity could be challenging due to the complex anatomical and geometrical irregularities caused by previous surgeries and spine degeneration. Virtual and 3D printed models have the potential to illuminate the unique and complex anatomical-geometrical problems found in these patients. Case Presentation: We present a case report with 6-months follow-up (FU) of a 71 year old female patient with severe sagittal and coronal malalignment due to repetitive discectomy, decompression, laminectomy, and stabilization surgeries over the last 39 years. The patient suffered from severe low back pain (VAS = 9, ODI = 80). Deformity correction by performing asymmetric 3-column pedicle subtraction osteotomy (PSO) and stabilization were decided as the required surgical treatment. To better understand the complex anatomical condition, a patient-specific virtual geometry was defined by segmentation based on the preoperative CT. The geometrical accuracy was tested using the Dice Similarity Index (DSI). A complex 3D virtual plan was created for the surgery from the segmented geometry in addition to 3D printed model. Discussion: The segmentation process provided a highly accurate geometry (L1 to S2) with a DSI value of 0.92. The virtual model was shared in the internal clinical database in 3DPDF format. The printed physical model was used in the preoperative planning phase, patient education/communication and during the surgery. The surgery was performed successfully, and no complications were registered. The measured change in the sagittal vertical axis was 7 cm, in the coronal plane the distance between the C7 plumb line and the central sacral vertical line was reduced by 4 cm. A 30⁰ degree correction was achieved for the lumbar lordosis due to the PSO at the L4 vertebra. The patient ODI was reduced to 20 points at the 6-months FU. Conclusions: The printed physical model was considered advantageous by the surgical team in the pre-surgical phase and during the surgery as well. The model was able to simplify the geometrical problems and potentially improve the outcome of the surgery by preventing complications and reducing surgical time.